Lost in the middle of the sea, found in the back of the shelf: A new giant species of Trachylepis (Squamata: Scincidae) from Tinhosa Grande islet, Gulf of Guinea - Ceríaco, Luis M. P. (Zootaxa, 2015)
A new species of Trachylepis is described from Tinhosa Grande islet, São Tomé e Príncipe, Gulf of Guinea. Tinhosa Grande islet is a small (20.5 ha), isolated desert islet used by several bird communities as a nesting place. The new species is distinguished from its congeners by its color pattern, size and lepidosis. Due to its limited geographical distribution the new species appears to be one of the most vulnerable vertebrate species on the planet. In this study we provide a brief discussion on the natural history of the new species, as well as conservation concerns and suggestions.